2021
DOI: 10.1155/2021/8109134
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect and Mechanism of Bone Morphogenetic Protein-4 on Apoptosis of Human Lens Epithelium Cells under Oxidative Stress

Abstract: Bone morphogenetic proteins (BMPs), a member of the transforming growth factor β (TGF-β) superfamily, are abundant in human ocular tissues and play an important role in lens development. Targeted deletion of BMP-4 in mice results in failure of lens placode formation. Following lens maturation, the formation of senile cataracts is demonstrably associated with free radical-related oxidative stress. Previous studies reported that BMPs play an antiapoptotic role in cells under oxidative stress, and the BMP-4 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Work in our laboratory showed that BMP-4 can block TGFβ2-induced EMT in rat lens epithelial explants by suppressing Smad2/3 nuclear translocation [109]. The protective effect of BMP-4 has been further demonstrated in the human lens epithelial cell lines (HLE-B3), where exogenous addition of BMP-4 blocked apoptosis of lens epithelial cells under H 2 O 2 -induced oxidative stress [110]. Intriguingly, small molecule agonists of BMPs, ventromorphins, were unable to suppress TGFβ2-induced lens EMT in rat lens explants, highlighting that not all approaches to promote BMP-signaling can block TGFβ2-induced lens EMT [109].…”
Section: Bmps In Cataract Preventionmentioning
confidence: 87%
“…Work in our laboratory showed that BMP-4 can block TGFβ2-induced EMT in rat lens epithelial explants by suppressing Smad2/3 nuclear translocation [109]. The protective effect of BMP-4 has been further demonstrated in the human lens epithelial cell lines (HLE-B3), where exogenous addition of BMP-4 blocked apoptosis of lens epithelial cells under H 2 O 2 -induced oxidative stress [110]. Intriguingly, small molecule agonists of BMPs, ventromorphins, were unable to suppress TGFβ2-induced lens EMT in rat lens explants, highlighting that not all approaches to promote BMP-signaling can block TGFβ2-induced lens EMT [109].…”
Section: Bmps In Cataract Preventionmentioning
confidence: 87%
“…Mitochondria, the cellular hub of energy metabolism, plays a central role in regulating intracellular OS. According to available studies, p38/MAPK [ 32 , 33 ] and JNK/ERK [ 33 , 34 ] pathways and relative effectors/regulators (including activating transcription factors (ATFs) [ 35 ], runt-related transcription factor 2 (Runx2) [ 34 ], caspase9 [ 36 ], etc.) were significantly suppressed by OS, resulting in the attenuation of osteoblast differentiation.…”
Section: Phenolic Compounds Regulate Btcsmentioning
confidence: 99%
“…The perfect machinery of the human natural lens is an absence of organelles and mitochondria is locked to the epithelial cells, consuming almost ninety percentage of the complete oxygen consumption, practically the lens is hypoxic, calculated to be 3 mmHg (~0.4%); at the end 0.2-2% of the oxygen is destiny to produce superoxide and stimulates the respiratory chain oxidative phosphorylation; meant to be able to describe the new potential solutions [4][5].…”
Section: Unwrapping Cataractsmentioning
confidence: 99%